PENGARUH DUKUNGAN SOSIAL TEMAN SEBAYA TERHADAP STRES AKADEMIK MAHASISWA KEDOKTERAN GIGI PADA SAAT PANDEMI - Zahara, Nabila; Dewi, Mahargyantari Purwani (LPPM Institut Pendidikan Nusantara Global, 2023)
Dental students are expected to become professional dentists. For this reason, the learning process that is carried out can be said to be not easy with many courses, tasks that must be completed immediately, and laboratory practices that must be followed. Coupled with the current pandemic situation, dental students must be able to adapt to new learning methods. The purpose of this study was to empirically examine the effect of peer social support on academic stress of dental students during a pandemic. The method used is quantitative. The sampling technique used in this study was purposive sampling. The characteristics of the samples taken were active dentistry students who followed online or hybrid learning methods and took courses supported by laboratory practices. Respondents of this study found 71 people. The measuring instrument of this study used symptoms of academic stress and aspects of peer social support. The data analysis technique used is simple regression. The results of the hypothesis test showed a significance value of 0.023 (p 0.050) and an R Square value of 0.072 was obtained. This shows the accepted hypothesis, namely the influence of peer social support on academic stress of dental students during a pandemic, where peer social support has an effect of 7.2% on academic stress, while the remaining 92.8% is influenced by other factors. outside of research.